Modeling the Distribution of Organic Coffee Supply Chain from JunÃn Region, Peru - Ramos, Edgar D.; Mesia, Ron; Cavero, Carlos; Vera, Brenda; Wu, Zilin (ExcelingTech, 2019)
This research uses Supply Chain (SC) data gathered during the distribution and transportation activities of organic coffee. The purpose of this research is to analyze different ways in which crop-chain solutions are adopted in the region of Junn, Peru. The disintegration of the SC is revealed, as each cooperative member works uncoordinatedly on his own leading to different results standards with high costs and low returns. The study focused on different entities from farmers to the port of Callao of an organic coffee supply chain where disintegration is constant. The paper describes a misaligned supply chain including poorly collaboration. All problems found will be an opportunity to develop a distribution model in the organic coffee supply chain of Junn region.